Chiral Separation of Tolterodine Tartrate Using Amylosed Base Immobilized Stationary Phase in LC Method - Ahirrao, V.K.; Patil, C.S.; Bembalkar, S.R.; Katariya, M.V.; Ubale, S.B.; Marathe, R.P.; Pawar, R.P. (Asian Journal of Chemistry, 2012)
High-performance liquid chromatographic method was developed and validated for chiral separation of tolterodine tartrate. It was achieved on Chiral pack IA (immobilized amylosed based polysaccharides stationary phase) using a mobile phase of hexane: 2-propanol: triethylamine: trifluroacetic acid (91:9:0.2:0.1 v/v) at a flow rate 1.1 mL/min. Resolution between S-tolterodine tartrate and R-tolterodine tartrate was found to be 2.9. Developed LC method was used for the quantification of S-tolterodine tartrate as chiral impurity in R- tolterodine tartrate. The developed method was extensively validated and proved to be robust. The calibration curve for S-tolterodine tartrate showed an excellent linearity over the concentrations range 0.1 to 10 μg/mL. The limit of detection and limit of quantification for S-tolterodine tartrate were 0.11 μg/mL and 0.34 μg/mL respectively. Average recovery of S-isomer was in the range of 97.30 to 101.59 %. S-tolterodine tartrate and R-tolterodine tartrate solutions in mobile phase were found to be stable for 48 h. The proposed method was short runtime, precise and accurate for quantitative determination of S-isomer in R-tolterodine tartrate in API and its solid oral dosage form.